The Need for National and State Ethics Laws in Indonesia: Perlunya Undang-Undang Etika Berbangsa dan Bernegara di Indonesia - Boerhan, Soebagio; Sidharta, Dudik Djaja (Rechtsidee, 2022)
The study of constitutional law does not only study positive law, but also includes national and state ethics. Indonesia actually has TAP MPR No. 4 on the Ethics of National Life. Although in its application the ethics of nation and state are still not effective in practice in society. This study aims to examine TAP MPR No. VI concerning the Ethics of National Life and its implementation in various aspects and future arrangements. This research is a normative legal research. Legal materials in this study include primary, secondary, and non-legal materials. The approach in this study uses a conceptual approach and a statutory approach. The results of the study confirmed that the implications of TAP MPR No. VI concerning the Ethics of National Life in constitutional law in Indonesia actually requires special arrangements in the Act so that it becomes the Law on the Ethics of National and State Life. The future implementation and regulation of the TAP MPR on National and State Ethics in Indonesian constitutional law can be carried out by establishing a Law on National and State Ethics which contains basic principles and is instrumentally and specifically determined by each agency, profession or group in society, combining the socialization of the four pillars of the MPR with the socialization of awareness of national and state ethics, and making awareness of national and state ethics as part of the national education system.